Sterility of Gauze Packed in One and Three Layer Layer Parchment Paper - Putri, Saskia Biyakto; Lestari, Endang Sri; Ciptaningtyas, Vincentia Rizke (Sains Medika: Jurnal Kedokteran dan Kesehatan, 2017)
Intoduction: Sterile gauze is one of the medical devices that are often used to prevent infection. Several things, one of them is materials for packaging, can affect the sterility of gauze. Parchment paper is one of the packaging materials for sterilization. The study was done to analyze the sterility of gauze packed with parchment paper one layer and three layers on the growth of microorganism.Method: This study was an experimental study with a quasi-experimental design. Samples were 60 gauze packed with one layer parchment paper and 60 gauze packed with three layers of parchment paper. The sterility of sterile gauze tested at weeks 0, 2 and 4. Results: There was no significant difference in the sterility of gauze packed with 1 layer of parchment paper on the growth of microorganisms at 0, 2, 4 weeks (p = 0.126). No significant difference in the sterility of sterile gauze packed with 3 layers of parchment paper at 0, 2, 4 weeks (p = 0.675). There was a significant difference in the sterility of sterile gauze packed with parchment paper 1 layer and 3 layers on the growth of microorganisms (p = 0.002).Conclusion There is a significant difference of sterile gauze packed with parchment paper 1 layer and 3 layers against the growth of microorganisms. The sterility of the packaged sterile gauze with a layer of parchment paper is better than the three layers.